Natively fat‐suppressed 5D whole‐heart MRI with a radial free‐running fast‐interrupted steady‐state (FISS) sequence at 1.5T and 3T. Issue 1 (27th August 2019) - Bastiaansen, Jessica A.M.; Piccini, Davide; Di Sopra, Lorenzo; Roy, Christopher W.; Heerfordt, John; Edelman, Robert R.; Koktzoglou, Ioannis; Yerly, Jérôme; Stuber, Matthias
Abstract : Purpose: To implement, optimize, and test fast interrupted steady‐state (FISS) for natively fat‐suppressed free‐running 5D whole‐heart MRI at 1.5 tesla (T) and 3T. Methods: FISS was implemented for fully self‐gated free‐running cardiac‐ and respiratory‐motion‐resolved radial imaging of the heart at 1.5T and 3T. Numerical simulations and phantom scans were performed to compare fat suppression characteristics and to determine parameter ranges (number of readouts [NR] per FISS module and TR) for effective fat suppression. Subsequently, free‐running FISS data were collected in 10 healthy volunteers and images were reconstructed with compressed sensing. All acquisitions were compared with a continuous balanced steady‐state free precession version of the same sequence, and both fat suppression and scan times were analyzed. Results: Simulations demonstrate a variable width and location of suppression bands in FISS that were dependent on TR and NR. For a fat suppression bandwidth of 100 Hz and NR ≤ 8, simulations demonstrated that a TR between 2.2 ms and 3.0 ms is required at 1.5T, whereas a range of 3.0 ms to 3.5 ms applies at 3T. Fat signal increases with NR. These findings were corroborated in phantom experiments. In volunteers, fat SNR was significantly decreased using FISS compared with balanced steady‐state free precession ( P < 0.05) at both field strengths. After protocol optimization, high‐resolution (1.1 mm 3 ) 5D whole‐heart free‐running FISS can be performed with effective fat suppression in under 8 min at 1.5T and 3T at a modest scan time increase compared to balanced steady‐state free precession. Conclusion: An optimal FISS parameter range was determined enabling natively fat‐suppressed 5D whole‐heart free‐running MRI with a single continuous scan at 1.5T and 3T, demonstrating potential for cardiac imaging and noncontrast angiography.